Using Social Media to Connect with University Constituents During a Campus Crisis: Application Among North Carolina Public and Private Colleges and Universities - Davis, Britt (My University, 2013)
An emergency, crisis, or controversy on the college or university campus can come at any moment. Sometimes, such as in the case of a weather related emergency, there is time to prepare, warn constituents, and take protective measures. Other situations, such as campus shootings, can come without warning. The crisis situation can seemingly come from nowhere and cause major disruption to normal campus life and routines. With over 4,400 public and private colleges and universities in the United States serving nearly 20 million students, emergency situations are inevitable. North Carolina colleges and universities managed several emergency situations in 2011 and 2012. Various media forms, including email, web updates, and social media tools such as Facebook and Twitter, played a significant role in each campus scenario. These tools were utilized to provide official university communications to institution constituents. Social media was extensively utilized in some situations. The purpose of this study is to examine the actual and potential use of social media among North Carolina’s institutions of higher education during emergency situations. The study was conducted through a review of existing literature and data obtained through a survey of communications professionals at the state’s 16 public and 35 private baccalaureate institutions. The study examines how university communications professionals use and perceive various communication methods, including social media use during crisis situations. The study also assesses differences in the perceptions and actual use of communications media and tools, with an emphasis on social media, among North Carolina’s public and private colleges and universities. Study findings serve as the basis for a social media crisis communications model and best practice recommendations. This study is significant because it helps to further enhance an understanding of the potential and actual use of social media among North Carolina’s institutions of higher education during emergency and crisis campus situations. On a practical level, this study also highlights various college and university social media crisis communications models and best practice recommendations.
Valdosta State University Dissertation by Britt Davis, May 2013.
Keywords: Social Media; Emergencies; North Carolina; Higher Education; Crisis; Campus Shooters; Facebook; Twitter; Communications; Technology; Public Administration